IFRS adoption and its influence on capital market in transition countries : The case of China - Xu, Ming; Procházka, David, 1979 říjen 10.-; Zárybnická Žárová, Marcela, 1959-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
Accounting is considered as a general economy and finance language which plays a significant role in the business society. The capital market is a key part of the economy which cannot get through without the development of accounting. In recent years, Accounting harmonization gains more and more awareness from some studies of accounting practice and theory which aims to increase the attractiveness of capital markets by reporting high-quality financial statements in the way of reduced financing costs.Based on the international standards of financial accounting, this essay focuses on observing the process of the Chinese accounting harmonization. Then, further analysis will be conducted on the comparability index between those two kinds of standards on the basis of capital market and return on net assets of public companies. This analysis is going to investigate the items of accounting which tend to significantly impact the features of the industry.
Vedoucí práce: David Procházka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses